2012
DOI: 10.1371/journal.pone.0042273
|View full text |Cite
|
Sign up to set email alerts
|

Foxp4 Is Dispensable for T Cell Development, but Required for Robust Recall Responses

Abstract: Transcription factors regulate T cell fates at every stage of development and differentiation. Members of the Foxp family of forkhead transcription factors are essential for normal T lineage development; Foxp3 is required for T regulatory cell generation and function, and Foxp1 is necessary for generation and maintenance of naïve T cells. Foxp4, an additional member of the Foxp family, is highly homologous to Foxp1 and has been shown to dimerize with other Foxp proteins. We report the initial characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Wiehagen et al found that FOXP4 is expressed in immature thymocytes and mature T lymphocyte subsets and it is dispensable for T cell development. However, FOXP4 is required for normal T cell cytokine robust recall responses (28). In addition, Long et al successfully replicated the association of rs1983891 (FOXP4) with prostate cancer and provide further support for association of the FOXP4 with prostate cancer in Eastern Asian populations (29).…”
Section: Discussionmentioning
confidence: 97%
“…Wiehagen et al found that FOXP4 is expressed in immature thymocytes and mature T lymphocyte subsets and it is dispensable for T cell development. However, FOXP4 is required for normal T cell cytokine robust recall responses (28). In addition, Long et al successfully replicated the association of rs1983891 (FOXP4) with prostate cancer and provide further support for association of the FOXP4 with prostate cancer in Eastern Asian populations (29).…”
Section: Discussionmentioning
confidence: 97%
“…FoxM1 appears to be important for T cell proliferation and impaired FoxM1 expression might diminish the proliferative potential of FoxO1−/− memory CD8 T cells (47). Loss of Foxp4 has been reported to impair cytokine production by LCMV-specific CD4 T cells (48), but the role of Foxp4 in regulating CD8 T cell memory is yet to be determined. The reduced recall response of FoxO1−/− memory CD8 T cells is also associated with diminished levels of cyclins (A2, D1 and F) and increased expression of anti-proliferative cyclin-dependent kinase inhibitors (p15 INK4B , p18 INK4c and p57 Kip2 ) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“… 47 Rs1983891 was located in intron 2 of FOXP4 (forkhead box P4), which is expressed in both thymocytes and peripheral CD4 (+) and CD8 (+) T-cells and is necessary for normal T-cell cytokine recall responses to antigen following pathogenic infection. 51 …”
Section: Geneticsmentioning
confidence: 99%